Vocabulary learning in EFL context: do primary school English Subject textbooks provide structured support? - Biseko, John Misana (Cogent education, 2025)
Vocabulary is recognised as a core aspect of EFL learning and communicative competency. To support this critical component of language proficiency, textbooks play a central role in EFL instruction and must be deliberately designed to foster learners’ acquisition of useful vocabulary. This study examined whether primary school EFL textbooks in Tanzania provide structured support for vocabulary uptake. The study was guided by two research objectives: to assess the supportive conditions for vocabulary learning provided in the sampled textbooks and to analyse the incremental advancement of vocabulary frequency levels across the textbooks. Using qualitative content analysis and quantitative corpus analysis, the results unveiled a clear intention to support vocabulary development through direct instructional activities. However, a comprehensive analysis revealed critical shortcomings that undermine incidental vocabulary learning—the necessary complement to intentional approaches. Issues such as limited recycling of target vocabulary, an overemphasis on only the most frequent 2,000 words, lack of systematic progression in lexical difficulty, and unsystematic selection of words to meet the 95% to 98% comprehension thresholds collectively call into question the textbooks’ overall effectiveness in cultivating vocabulary knowledge. The implications of the findings, their limitations, and suggestions for future research are discussed.